Concept of spirituality in philosophical heritage of S. Krymsky - Кошетар, У. П. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article studies the problem of spirituality in globalized society represented in the philosophical heritage of Sergei Krymsky. Thefeatures of the category of "spirituality" are revealed and its analysis is given on the basis of philosophical reflections of the outstandingUkrainian thinker. It is concluded, that Sergei Krymsky is an author of the holistic concept of spirituality.